2023
DOI: 10.1002/adhm.202202368
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Properties and Pharmacokinetics of Temporarily PEGylated Onc72 Prodrugs

Abstract: The favorable properties of antimicrobial peptides (AMPs) to rapidly kill pathogens are often limited by unfavorable pharmacokinetics due to fast degradation and renal clearance rates. Here, a prodrug strategy linking proline‐rich AMP Onc72 to polyethylene glycol (PEGs) with average molecular weights of 5 and 20 kDa via a peptide linker containing a protease cleavage site is tested for the first time in vivo. Onc72 is released from these 5k‐ and 20k‐prodrugs in mouse serum with half‐life times (t1/2) of 8 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…All PrAMPs tested, including the reverse and scrambled peptides, showed no significant hemolytic activity compared to the untreated control (addition of PBS) up to concentrations of 600 mg/L (234 to 285 μmol/L), as previously reported for some PrAMPs (Czihal et al, 2012;Krieger et al, 2021;Mohammed et al, 2023), in contrast to a strong hemolytic effect observed for amphotericin B already at the lowest concentration tested (125 mg/L; 135 μmol/L) (Supplementary Figure S5).…”
Section: Cytotoxicity and Hemolytic Activitysupporting
confidence: 75%
See 1 more Smart Citation
“…All PrAMPs tested, including the reverse and scrambled peptides, showed no significant hemolytic activity compared to the untreated control (addition of PBS) up to concentrations of 600 mg/L (234 to 285 μmol/L), as previously reported for some PrAMPs (Czihal et al, 2012;Krieger et al, 2021;Mohammed et al, 2023), in contrast to a strong hemolytic effect observed for amphotericin B already at the lowest concentration tested (125 mg/L; 135 μmol/L) (Supplementary Figure S5).…”
Section: Cytotoxicity and Hemolytic Activitysupporting
confidence: 75%
“…The plates were centrifuged (5 min, 1,000 × g, 4°C), the supernatants (100 μL) were transferred to flat-bottom 96-well plates, and the absorbance was recorded at 405 nm on a microplate reader (PARADIGM™, Molecular Devices). PBS was used as negative control, and a serial dilution of triton X-100 from 0.1 to 0.00078% was used as a positive control ( Czihal et al, 2012 ; Mohammed et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Novel design techniques, including peptide sequence modification, development of self‐assembled AMPs, and utilization of biomaterial carriers, hold the potential to address these challenges. For instance, cyclic and PEGylated AMPs demonstrate increased resistance to protease degradation, significantly improving their stability (Malde et al., 2019; Mohammed et al., 2023). Self‐assembled AMPs in the form of nanofibres, nanoparticles and nanoribbons exhibit additional functions whilst enhancing their permeability (Xie et al., 2022).…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%